Society for Immunotherapy of Cancer consensus statement on immunotherapy for the treatment of bladder carcinoma - Ashish M. Kamat (Journal for ImmunoTherapy of Cancer, 2017)
Abstract The standard of care for most patients with non-muscle-invasive bladder cancer (NMIBC) is immunotherapy with intravesical Bacillus Calmette-Guérin (BCG), which activates the immune system to recognize and destroy malignant cells and has demonstrated durable clinical benefit. Urologic best-practice guidelines and consensus reports have been developed and strengthened based on data on the timing, dose, and duration of therapy from randomized clinical trials, as well as by critical evaluation of criteria for progression. However, these reports have not penetrated the community, and many patients do not receive appropriate therapy. Additionally, several immune checkpoint inhibitors have recently been approved for treatment of metastatic disease. The approval of immune checkpoint blockade for patients with platinum-resistant or -ineligible metastatic bladder cancer has led to considerations of expanded use for both advanced and, potentially, localized disease. To address these issues and others surrounding the appropriate use of immunotherapy for the treatment of bladder cancer, the Society for Immunotherapy of Cancer (SITC) convened a Task Force of experts, including physicians, patient advocates, and nurses, to address issues related to patient selection, toxicity management, clinical endpoints, as well as the combination and sequencing of therapies. Following the standard approach established by the Society for other cancers, a systematic literature review and analysis of data, combined with consensus voting was used to generate guidelines. Here, we provide a consensus statement for the use of immunotherapy in patients with bladder cancer, with plans to update these recommendations as the field progresses.